Effects of hydroxyethyl starch (HES 130/0.42) on endothelial and epithelial permeability in vitro. (October 2019) - Wong, Yuk Lung; Lautenschläger, Ingmar; Zitta, Karina; Hummitzsch, Lars; Parczany, Kerstin; Steinfath, Markus; Weiler, Norbert; Albrecht, Martin
Abstract: Hydroxyethyl starch (HES) is employed to sustain normovolemia in patients. Using a perfused organ model, we recently showed that HES impairs the intestinal barrier which is constituted of endothelial and epithelial cell layers. However, the target cells and molecular actions of HES in the intestine are mainly unknown. Employing a model of human endothelial (HUVEC) and intestinal epithelial cells (Caco-2), we investigated the impact of HES, albumin and HES/albumin on cellular integrity/permeability and evaluated underlying molecular mechanisms. Monolayers of HUVEC and Caco-2 were cultured with HES (3%), albumin (3%) or HES/albumin (1.5%/1.5%). Integrity and permeability of the cell layers were evaluated by FITC-dextran transfer, measurements of cell detachment, vitality, cell volume, LDH release and caspase-3/7 activity. Cellular mechanisms were analyzed by Westernblotting for P-akt, P-erk, claudin-3 and I-FABP. HES application resulted in higher numbers of non-adherent/floating HUVEC cells (P<0.05) but did not change vitality or cell volume. Both, HES and HES/albumin increased the permeability of HUVEC monolayers (P<0.001), while LDH release, caspase-3/7 activity, akt/erk phosphorylation and claudin-3 expression were not affected. HES and HES/albumin did not change any of the parameters in cultures of Caco-2 cells. HES is able to disturb the integrity of the endothelial but not the epithelial barrier in vitro. HES effects are unrelated to cell damage and apoptosis but may involve reduced cell-cell or cell-matrix adhesion. Highlights: Hydroxyethylstarch (HES) containing solutions are employed to sustain normovolemia in patients. We have recently shown that HES impairs the intestinal barrier integrity in a perfused organ model. Employing human endothelial and epithelial cells we investigated the impact of HES on cellular integrity/permeability. Clinically relevant concentrations of HES disturb the integrity of the endothelial but not the epithelial barrier. HES effects are unrelated to cell damage and apoptosis but may involve reduced cell-cell or cell-matrix adhesion.